Predictors of recurrent course of endometrial hyperplasia without atypia in women of reproductive age - Mekan R. Orazov; Viktor E. Radzinsky; Marina B. Khamoshina; Lyudmila M. Mikhaleva; Irina A. Mullina; Yuliia S. Artemenko (LLC "MEDIAFORMAT", 2023)
Aim. To establish predictors of recurrent course of endometrial hyperplasia (EH) without atypia in women of reproductive age. Material and methods. A retrospective analysis of 180 patients of reproductive age was performed on the basis of the Department of Obstet-rics and Gynecology with a course of perinatology at the Patrice Lumumba Peoples' Friendship University of Russia in Semashko Clinical Hospital "RZD-Medicine" in 2020-2023. During the study, two cohorts of patients were formed depending on the course of EH: group 1 - the main group (n=95) was represented by patients with morphologically verified recurrent EH without atypia during a year of follow-up (1 or more episodes of relapse), group 2 - comparison (n=85) - patients with morphologically verified EH without a history of atypia, with no recurrence of hyperplasia during the year. The average age of patients in the studied cohort was 43±3.0 years (comparison groups - 40±2.0 years). Results. In a cohort of patients suffering from morphologically confirmed recurrent EH without atypia, a high incidence of the following predic-tors was established during the year: refusal/absence of medication in the anamnesis - 32.2%, duration of therapy (less than 6 months) - 23.2%, cyclic mode of progestogen use (from the 14th to the 26th day of menstrual cycle - MC/from 16 on the 26th day of the MC) - 15.8%. Patients with recurrent EH were significantly more likely to be obese in 45.3%, arterial hypertension - 38.9%, severe vitamin D deficiency - 32.6%, vitamin D deficiency - 40%, chronic endometritis - 41.1%. Conclusion. Predictors of recurrent course of EH without atypia in women of reproductive age are: refusal/absence of taking medication in anamnesis (odds ratio - OR 39.909; 95% confidence interval - CI 4.899-278.068), duration of therapy less than 6 months (OR 12.507; 95% CI 2.843-55.015), cyclic mode of progestogen use - from the 14th to the 26th day of the MC/from the 16th to the 26th day of the MC (OR 8.893; 95% CI 1.966-40.229). Patients with recurrent EH were significantly more likely to have severe vitamin D deficiency (OR 13.466; 95% CI 5.323-34.068), chronic endometritis (OR 4.237; 95% CI 2.032-8.833), hypertension (OR 3.881; 95% CI 1.858-8.801), obesity (OR 2.368; 95% CI 1.259-4.453), vitamin D deficiency (OR 1.574; 95% CI 0.814-3.045). Prevention of non-atypical hyperplasia with progestogens and lifestyle mod-ification carries a wide range of benefits, including those associated with a favorable fertility prognosis.